ACCOUNTABILITY FOR IMPLEMENTING ELECTRONIC PROGRAMS FOR MUTUAL COOPERATION STALLS (E-WARONG) DI KECAMATAN BANYUMANIK KOTA SEMARANG - Mavita Anarizka; Nina Widowati (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2019)
The problem of poverty is a problem faced and is of concern to many people in the world. One of the Government programs to alleviate poverty that was just launched in 2015 in Semarang is Electronic Warong mutual assistance or eWarong is an electronic mutual cooperation program. This research was conducted to find out accountability in the E-Warong (Electronic Grocery Mutual Cooperation) program in Banyumanik District. To measure the accountability of the E-Warong program using the Probity and legality accountability dimensions, Process accountability, Performance accountability, Program accountability, Policy accountability, Financial accountability and the inhibiting factors in the accountability of the E-Warong Program. The method used is a case study with a qualitative approach. Data collection techniques used were interviews, observation, and documentation. The results in the field show that the targets of the E-Warong program have not yet been achieved, lack of human resources, members' creativity in dealing with problems are not developed and the lack of response of leaders in responding to problems. Result on the research that has been carried out the accountability of the implementation of the E-Warong Program (Electronic Gotong Royong Warung) in Banyumanik Subdistrict, it has not been optimally seen from the dimensions of accountability that have been measured and there are obstacles in the implementation of the program.